PENINGKATAN SIKAP MAWAS DIRI DAN TANGGUNG JAWAB MELALUI PENDAMPINGAN PERTAHANAN DIRI BAGI SISWA SEKOLAH DASAR DI KECAMATAN GUNUNGPATI SEMARANG - Setiawan, Ipang; Abdulaziz, Moch Fahmi; Billiandri, Bhayu; Dharmawan, Dhimas Bagus (Jurnal Pengabdian Masyarakat AbdiMas, 2017)
AbstractThe phenomenon of violence and abuse against women and children conducted by the grown man even his own peers is indeed quite troubling indeed. The possible bad events that is against the development of the psychology of the childs attitude, such as lack of self-confidence, responsibility and confidence. Based on these problems the purpose of activity of this devotion is to provide mentoring in self-defense on elementary school children based on the values of the characters. The method of implementation of the activities in the form of 1) Socialization the dangers of abuse and sexual violence and 2) Mentoring children through training self defense martial arts pencak silat that its activities were given the assignment of routine activities that lead to such the demands of grain characters (such as self-reliance, introspective, responsibility, caring, and others). The result of this outreach activity is students know and understand the dangers of abuse and sexual violence, the increased ability of introspective attitude and responsibility with the mastery of skills in basic techniques of pencak silat at the students, students are able to perform the technique of punch, hindaran, block, and kicks (next, next, and Crescent) to confront such dangers. Keywords: improved attitudes,  mentoring self defense, elementary school students AbstrakFenomena kekerasan dan pelecehan terhadap anak dan wanita yang dilakukan oleh pria dewasa bahkan teman sebayanya sendiri memang sungguh cukup meresahkan. Kejadian tersebut memungkinan berdampak buruk yaitu terhadap perkembangan psikologi sikap anak, seperti kurangnya rasa percaya diri, tanggungjawab dan percaya diri. Berdasarkan permasalahan tersebut tujuan kegiatan pengabdian ini adalah memberikan pendampingan pertahanan diri pada anak sekolah dasar yang berbasiskan pada nilai-nilai karakter. Metode pelaksanaan kegiatan berupa 1) Sosialisasi bahaya pelecehan dan kekerasan seksual dan 2) Pendampingan pertahanan diri anak melalui pelatihan beladiri pencak silat yang kegiatannya diberi penugasan rutin melakukan kegiatan yang mengarah seperti tuntutan butir karakter (seperti kemandirian, mawas diri, tanggungjawab, kepedulian, dan lain-lain). Hasil dari kegiatan pengabdian masyarakat ini adalah siswa mengetahui dan memahami bahaya pelecehan dan kekerasan seksual, peningkatan kemampuan sikap mawas diri serta tanggung jawab dengan adanya penguasaan keterampilan teknik dasar pencak silat pada siswa-siswi, siswa mampu melakukan teknik pukulan, hindaran, tangkisan, dan tendangan (samping, sabit, dan depan) untuk menghadapi bahaya tersebut. Kata kunci: peningkatan sikap; pendampingan pertahanan diri; siswa sekolah dasar